Chemical biology approaches to drug discovery and development to targeting disease - Civjan, Natanya (Wiley, 2012)
"Based on the award winning Wiley Encyclopedia of Chemical Biology, this book provides a fairly general overview of the role of chemical biology in drug discovery and development and in understanding biological mechanisms of common diseases"--